The effect of Tabata training program on physical and motoric characteristics of soccer players - Afyon , Yakup Akif; Mulazimoglu, Olcay; Celikbilek, Sinan; Dalbudak, İbrahim and Kalafat, Cagan (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to examine the effect of Tabata training on some motoric performances of soccer players. Methods: Eighteen male amateur soccer players voluntarily participated in the study. The selected participants were randomly divided into two groups ‘EG’ (age: 22.78±3.38 years) underwent Tabata Training (TT) group (n=9) and group ‘CG’ (age: 21.44±2.30 years) acted as control group (n=9). In addition to their regular training, EG performed eight different core and plyometric exercises, each of which lasted for 4 minutes, as 20 seconds of work and 10 seconds of recovery. CG was not exposed to any specific training but they participated in regular activities. The following variables were selected to determine the effect of TT on the physical and motoric characteristics of the players: body fat percentage (BF%), standing long jump (SLJ), sit-and-reach test (SRT), flamingo balance test (FBT), back strength (BS), leg strength (LS) and zig-zag agility test (ZAT). The data were obtained from these tests of both group players with the pre-test and post-test methods. After performing normal distribution tests of all data, pre-post-test comparison analyses were interpreted at .05 significance level. Results: There was a significant difference between EG’s SLJ, BS and LS pre and post-tests averages (p<.05). There was a significant difference between CG’s BS pre and post-tests averages (p<.01). Conclusion: Eight-week TTs have improved players’ strength characteristics. However, although there was an improvement in skills such as flexibility, balance and agility, it was not at a significant level.